2023
DOI: 10.4070/kcj.2023.0083
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Features of Korean Inherited Arrhythmia Probands

Abstract: Author's summary Inherited arrhythmia is a more common cause of sudden cardiac arrest in Asian population, yet less is known of genetic background compared to western population. Certain clinical differences were found in the three most common disease: idiopathic ventricular fibrillation (IVF), Brugada syndrome (BrS), and long QT syndrome (LQTS). Patients detected with certain genotype resulted lower left ventricular ejection fraction compared to those without detected genotype (54.7±11.3 vs. 59.3±9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Although the main IAs, such as J wave syndrome, 5) BrS, 6) and acquired LQTS, 7) are common in Asian populations, little is known about its clinical characteristics and genetic background in Asian populations. This study 8) is a retrospective, multicenter cohort study in Korean, which investigated the clinical characteristics of Korean IA probands and further analyze the genetic findings via next-generation sequencing (NGS). It showed that the most common disease entity was IVF (36.2%), followed by BrS (35.8%) and LQTS (20.4%) in Korean IA cohort.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the main IAs, such as J wave syndrome, 5) BrS, 6) and acquired LQTS, 7) are common in Asian populations, little is known about its clinical characteristics and genetic background in Asian populations. This study 8) is a retrospective, multicenter cohort study in Korean, which investigated the clinical characteristics of Korean IA probands and further analyze the genetic findings via next-generation sequencing (NGS). It showed that the most common disease entity was IVF (36.2%), followed by BrS (35.8%) and LQTS (20.4%) in Korean IA cohort.…”
mentioning
confidence: 99%
“…The genetic analysis via NGS reported by Jeong et al 8) show clinical characteristics and genetic findings of Korean IA probands. From the data presented, it was possible to understand characteristics of the three common IAs of Koreans such as IVF, BrS, and LQTS.…”
mentioning
confidence: 99%